Molecular landscape and clinical significance of exon 11 mutations in KIT gene among patients with gastrointestinal stromal tumor: a retrospective exploratory study - Zhao, Ruihua; An, Tianqi; Liu, Min; Zhou, Yanan; Li, Rui; Jiang, Guozhong; Li, Jing; Cao, Xinguang; Zong, Hong (Frontiers in Oncology, 2023)
Objective This aim of this study was to investigate the prognostic significance of KIT exon 11 mutation subtypes in patients with GISTs. Methods A total of 233 consecutive patients diagnosed with GISTs at the First Affiliated Hospital of Zhengzhou University from January 2013 to August 2018 were included in this study. The prevalence and mutation landscape of exon 11 in KIT was presented. The clinicopathological characteristics and prognosis among the different mutation subtypes were analyzed. All the statistical analyses were performed by SPSS22.0. Results Somatic mutational analysis indicated that point mutations were the most frequently detected mutations followed by deletions & compound mutations and insertion and tandem duplication mutations in the stomach. Point mutations showed a low mitotic count and a high risk of recurrence, and deletions and compound mutations have a high mitotic count while insertions and tandem duplication mutations showed a low mitotic count with an intermediate recurrence risk. Point mutations and deletions frequently occurred in sequence region codons 550-560 of exon 11, while compound mutations, insertion, and tandem duplication were mainly detected in codons 557-559, 572-580, and 577-581, respectively. The multi-variation analysis demonstrated that tumor diameter and high recurrence risk groups had worse prognostic values. However, mutation types were not significant predictors of relapse-free survival (RFS) in GISTs. Survival analysis suggested no significant difference in RFS between the 557/558 deletion and the other deletions. Conclusion This study suggested that mutations in exon 11 of the KIT gene were common with intermediate/high recurrence risk in GISTs patients. Tumor diameter ≥5 cm, and deletions mutations might predict a worse prognosis.